Different associations of varying types of Vitamin E and cognitive function in older adults with or without APOE Ɛ4 allele. (20th December 2022) - Liu, Xiaoran; Beck, Todd; Dhana, Klodian; Evans, Denis A; Rajan, Kumar B
Abstract: Background: Different forms of vitamin E may have a different association with cognitive function, which might vary by the APOE E4 allele status. We aim to examine vitamin E from different sources and in varying forms and their relation to cognitive decline among those with and without the APOE E4 allele. Methods: We included 2, 014 participants from the Chicago Health and Aging Project (62% African Americans, 63% female). Global cognition was assessed using a composite score of episodic memory, perceptual speed, and the MMSE. Diet was assessed by a 139‐item FFQ. APOE genotype was assessed by hME Sequenom mass‐array platform. Mixed models were adjusted for age, sex, education, smoking status, calorie intake, alcohol consumption, use of supplements, time since baseline, and the interaction term of time with each covariate. Results: A higher dietary vitamin E was associated with slower cognitive decline. Those in the highest quintile of dietary vitamin E intake had 28% slower cognitive decline than the lowest quintile (β = 0.014, p = 0.02). A higher intake of dietary αlpha‐tocopherol was associated with slower cognitive decline in participants with APOE E4 allele, but not among those without. In participants with APOE E4 allele and in the highest quintile of alpha‐tocopherol intake had a 16.4% slower rate of global cognitive decline than those in the lowest quintile (β = 0.015, p = 0.0015). A higher intake of delta‐tocopherol was associated with a slower decline in individuals without the APOE E4 allele only. Among those without the APOE E4 allele and in the highest quintile, the rate of global cognitive decline was slower by 22% than the lowest quintile (β = 0.012, p = 0.0014). We found no significant associations between beta‐ and gamma‐ tocopherol intakes and cognitive decline among those with and without the APOE E4 allele. Conclusion: Our study found a positive association of alpha‐tocopherol with cognitive decline among those with the APOE E4 allele and delta‐tocopherol with the decline in those without the APOE E4 allele. Our findings suggest that different forms of vitamin E might have a different association with cognitive decline in older adults depending on their APOE E4 allele status.